Analisis Kebijakan Zonasi: Upaya Pemerataan Pendidikan di Indonesia - Nurohman, Fajar; Goro, Siti Fatimah; Harahap, Chisa Belinda (Gunung Djati Conference Series, 2025)
The zoning system in Indonesia's education aims to improve access and equity through a location-based approach. This policy seeks to eliminate the stigma between "favorite" and "non-favorite" schools while reducing social disparities in student admissions. This study employs a qualitative approach using secondary data analysis through literature review, including official documents and academic research. Findings indicate that the zoning system promotes equitable access to education, reduces elitism stigma, and encourages improved educational facilities in various regions. However, its implementation faces challenges such as inadequate facilities in non-favorite schools and resistance from the community. With strong legal support, transparency, and continuous evaluation, the zoning system can serve as a strategic tool for advancing social justice. The study recommends enhancing educational infrastructure, engaging the community, and conducting regular evaluations to ensure the long-term success of the zoning policy.